Polymer green flame retardants - Papaspyrides, Constantine D.; Kiliaris, Pantelis (Elsevier, 2014)
Polymer Green Flame Retardants covers key issues regarding the response of polymers during fire, the mechanisms of their flame retardation, the regulations imposed on their use, and the health hazards arising from their combustion. Presenting the latest research developments, the book focuses in particular on nanocomposites, believed to be the most promising approach for producing physically superior materials with low flammability and ecological impact. The fire properties of nanocomposites of various matrixes and fillers are discussed, the toxicological characteristics of these materials are analyzed.